1990
DOI: 10.1007/bf00241630
|View full text |Cite
|
Sign up to set email alerts
|

Major histocompatibility complex class I genes of Peromyscus leucopus

Abstract: Class I genes of the Peromyscus leucopus major histocompatibility complex (MhcPele) were examined by Southern blot hybridization, genomic cloning, and DNA sequencing. At least three distinct subtypes of Pele class I genes were discerned, which we have designated Pele-A, B, and C. The nucleotide sequences of exon 5-containing regions (encoding the transmembrane domain) suggested that Pele-A genes are homologs of mouse H-2K, D, L, and Q genes and that Pele-B genes correspond to mouse Tla genes. The Pele-C genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1991
1991
1994
1994

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 28 publications
1
13
0
Order By: Relevance
“…The myomorph rodent Peromyscus leucopus (family Cricetidae) provides an ideal model from which to view the evolution of MHC gene diversity since it is quite divergent from Rattus and Mus (family Muridae) but contains an MHC (MhcPele) with loci clearly homologous to the major H-2 class I and II gene subtypes (16,17). To understand the evolution of MHC class I loci, we have initially focused upon the transmembrane domain (TM)-encoding exon (exon 5).…”
mentioning
confidence: 99%
“…The myomorph rodent Peromyscus leucopus (family Cricetidae) provides an ideal model from which to view the evolution of MHC gene diversity since it is quite divergent from Rattus and Mus (family Muridae) but contains an MHC (MhcPele) with loci clearly homologous to the major H-2 class I and II gene subtypes (16,17). To understand the evolution of MHC class I loci, we have initially focused upon the transmembrane domain (TM)-encoding exon (exon 5).…”
mentioning
confidence: 99%
“…6). Homologs of M1, M2, and 344 can be found in Peromyscus leucopus (Crew et al 1990; C.-R. Wang et al, in preparation) and homologs of 341, M2, M3, and M4 can be identified in rats Wang et al 1991 a). Homologs of M1, M2, and 344 can be found in Peromyscus leucopus (Crew et al 1990; C.-R. Wang et al, in preparation) and homologs of 341, M2, M3, and M4 can be identified in rats Wang et al 1991 a).…”
Section: Discussionmentioning
confidence: 98%
“…Orthologous HLA and H-2 class II loci are more apparent because these genes, unlike class I genes, probably evolved through direct descent (Lundberg & McDevitt, 1992). As with haplotypic variation, there are large differences between species in the number of class I antigen-encoding loci ranging from fifty to sixty in Peromyscus leucopus and Rattus (Crew et al, 1990;Jameson et al, 1990) to seven in minature swine . The proposition here is that MHC class I gene diversity between species mirrors the profound interspecific diversity of life history patterns.…”
Section: Structure and Diversity Of Mhcsmentioning
confidence: 96%